Contribution of Research on Food and Horticultural Crops in Indonesia: an Economic Analysis - Evenson, R. E.; Abdurachman, Edi; Hutabarat, Budiman; Tubagus, Achmad C. (Economics and Finance in Indonesia, 1997)
.